Understanding the Growth and Trend Patterns of Palm Oil Imports in India: An Innovative Trend Analysis - , K. Naga Latha; , V. Srinivasa Rao; , C. Sarada; , A. Amarender Reddy; , K. N. Sreenivasulu (Archives of Current Research International, 2024)
Aim: India, with its large population, is one of the world's largest consumers of edible oils, and palm oil is a major component of this consumption. The objective of the study was to understand the growth and trend patterns of palm oil imports in India. Data Description: Monthly palm oil imports to India in terms of quantity from April 2007 to March 2023 was collected from various sources, including ICT Trade Map and UNCOMTRADE, based on the six-digit Harmonized System (HS) code. Methodology: Various parametric (Linear regression) and non-parametric (Modified Mann-Kendall’s Test, Sen’s slope and Innovative Trend analysis) approaches used for analyzing the trend in the India’s palm oil imports quantity. Results: The analysis revealed a mixed trend in palm oil imports, with a weak but definite pattern indicated by the linear regression analysis (R² = 0.1079). The Modified Mann-Kendall test identified significant growth in August and September, while the Innovative Trend Analysis highlighted strong increasing trends in February, March, April, and August, with September showing the most significant import growth. Conclusion: These findings underscore the importance of monitoring and understanding palm oil import trends for policymakers, traders, and stakeholders in the edible oil industry.